Carrier Multiplication in Silicon Nanocrystals: Theoretical Methodologies and Role of the Passivation. Issue 12 (15th November 2017) - Marri, Ivan; Govoni, Marco; Ossicini, Stefano
Abstract : Carrier multiplication is a non‐radiative recombination mechanism that leads to the generation of two or more electron–hole pairs after absorption of a single photon. By reducing the occurrence of dissipative effects, this process can be exploited to increase solar cell performance. In this work, we introduce two different theoretical fully ab initio tools that can be adopted to study carrier multiplication in nanocrystals. The tools are described in detail and compared. Subsequently, we calculate carrier multiplication lifetimes in H‐ and OH‐terminated silicon nanocrystals, pointed out the role played by the passivation on the carrier multiplication processes. Abstract : The Si 35 ( OH ) 36 is depicted in the left part of the figure. On the right, we schematize the carrier multiplication decay process ignited by the relaxation of a hole.